Description of a new species of Fannia Robineau-Desvoidy, 1830 (Diptera: Fanniidae) and distribution records of the genus from the Caucasus Mountains - Pont, Adrian C. (Zootaxa, 2015)
A new species, Fannia caucasica sp. nov., is described from localities in Georgia and Armenia between 1600 and 2200 m. In addition, previous literature on the genus Fannia Robineau-Desvoidy, 1830 in the Caucasus Mountains is reviewed, and records are given for 15 species from Armenia and Georgia, of which nine are new records for Armenia and seven are new records for Georgia.